2014
DOI: 10.1016/j.ecresq.2014.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive development of young dual language learners: A critical review

Abstract: Dual language exposure and bilingualism are relatively common experiences for children. The present review set out to synthesize the existing research on cognitive development in bilingual children and to identify the gaps and the methodological concerns present in the existing research. A search of major data bases for research conducted with typically-developing, preschool-age dual language learners between 2000-2013 yielded 102 peer-reviewed articles. The existing evidence points to areas of cognitive devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
210
1
14

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(231 citation statements)
references
References 106 publications
6
210
1
14
Order By: Relevance
“…50, No. 9, 2242-2254 0012-1649/14/$12.00 http://dx.doi.org/10.1037/a0037161 2242 graphically similar monolingual children in numerous domains of cognitive functioning, especially those related to inhibitory/cognitive control and metalinguistic awareness (see Barac, Bialystok, Castro, & Sanchez, 2014, for a review). Although it is clear that being fully bilingual is an advantage, and that early English proficiency is helpful, the processes and predictors that help ELLs learn English and become bilingual, especially among young children in poverty, are not at all clear.…”
mentioning
confidence: 99%
“…50, No. 9, 2242-2254 0012-1649/14/$12.00 http://dx.doi.org/10.1037/a0037161 2242 graphically similar monolingual children in numerous domains of cognitive functioning, especially those related to inhibitory/cognitive control and metalinguistic awareness (see Barac, Bialystok, Castro, & Sanchez, 2014, for a review). Although it is clear that being fully bilingual is an advantage, and that early English proficiency is helpful, the processes and predictors that help ELLs learn English and become bilingual, especially among young children in poverty, are not at all clear.…”
mentioning
confidence: 99%
“…First, being bilingual has been broadly construed in research on bilingualism and cognition and does not refer to equal mastery in or equal amount of exposure to two languages. In fact, research has shown that individuals who are equally fluent in two languages are rare [49]. Furthermore, research with typically-developing children has shown that children with limited but regular exposure to a second language enjoyed some bilingual advantage [50].…”
Section: Resultsmentioning
confidence: 99%
“…Depuis, un nombre considérable d'études a exploré un large éventail de capacités cognitives et langagières qui se développent en fonction du bilinguisme. De nombreux avantages cognitifs, de nature verbale et non verbale, liés à l'expérience bilingue à l'enfance ont été identifiés (voir par exemple, Abutalebi & Clahsen, 2015;Barac, Bialystok, Castro, & Sanchez, 2014;Calvo & Bialystok, 2014;Crivello et al, 2016;Haznedar, 2015;Kempert, Saalbach, & Hardy, 2011;Kroll & Bialystok, 2013;Nicolay & Poncelet, 2013). Dans le domaine du langage, les capacités qui relèvent de la conscience métalinguistique, concept qui a attiré l'attention de nombreux linguistes et psycholinguistes (pour une revue, voir Jessner, 2006;Pinto & El Euch, 2015) occupent une place privilégiée.…”
Section: Introductionunclassified
“…: Brédart & Rondal, 1982;Donaldson, 1978;Hakes, 1980;Karmiloff-Smith, 1992;Tunmer, Pratt, Herriman, 1984) mettent l'accent sur les aspects généraux de la dimension métalinguis-tique, comme étant basée sur des processus d'abstraction croissante, la plupart des travaux récents (ex. : Antoniou, Grohmann, Kambanaros, & Katsos, 2016;Barac et al, 2014;Blom et al, 2014;Kroll & Bialystok, 2013) sont plutôt basés sur la conceptualisation de Bialystok (2001Bialystok ( , 2004Bialystok ( , 2009Bialystok ( , 2011Bialystok ( , 2015. En effet, Bialystok refuse une vision monolithique de la conscience métalin-guistique.…”
Section: Introductionunclassified